فاعلية برنامج تدريبي لتحسين مهارات التواصل غير اللفظي لدى الطفل التوحدي - خروبي, أحمد; بوضياف, نادية (جامعة الوادي - University of Eloued, 2021)
ملخص: هدفت الدراسة الحالية إلى التعرف على فاعلية برنامج تدريبي مقترح قائم على التقليد والانتباه المشترك لتحسين مهارات التواصل غير اللفظي لدى الأطفال ذوي اضطراب طيف التوحد بمدينة غرداية، و تم استخدام المنهج التجريبي بتصميم شبه التجريبي ذو المجموعتين التجريبية و الضابطة بقياس قبلي و بعدي لتحقيق أهداف الدراسة، كما تكونت عينة الدراسة من (16) طفلا توحديا اختيروا بالطريقة العمدية، و للتأكد من فاعلية البرنامج، تم تطبيق مقياس مهارات التواصل غير اللفظي على عينة الدراسة، قبل و بعد تطبيق البرنامج على العينة التجريبية، لمعرفة التغير الذي طرأ على مجموعة البحث، و بعد جمع البيانات و معالجتها إحصائيا، توصلت النتائج الى أنه يوجد فاعلية للبرنامج التدريبي المقترح لتحسين مهارات التواصل غير اللفظي لدى عينة الدراسة التجريبية. Abstract: The aim of the present study was to identify the effectiveness of a proposed training program based on imitation and joint attention to enhance non verbal communication skills among children with autistic spectrum disorder in the city of Ghardaïa, the experimental methodology was selected and the “two group, Pre-test and Post-test Design” was used. The sample of the present study consists of (16) autistic children were chosen in purposive way, to ensure the effectiveness of the program, the non verbal communication skills scale was applied by the researcher to the sample of the study, before and after the application of the proposed program to identify the change in the research group, after the data were collected and analyzed, the findings of the study revealed that the proposed training program was effective on enhancing non verbal communication skills on the sample of the study.
مقال
Keywords: مهارات التواصل غير اللفظي ; اضطراب طيف التوحد ; التقليد ; الانتباه المشترك; non verbal communication skills; autism spectrum disorder; imitation; joint attention.